1988
DOI: 10.1111/j.1095-8649.1988.tb05333.x
|View full text |Cite
|
Sign up to set email alerts
|

Size characteristics and diet of emergent chinook salmon in a small, stable, New Zealand stream

Abstract: The emergence timing, quality and diet of chinook salmon, Oncorhynchus ishawyrschn, fry were studied as they emerged from ten natural redds. The impact of selected environmental factors on emergence was studied also. Samples of fry were obtained daily using redd traps.The mean period of total emergence for redds with more than 450 fry emerging was 44.8 days (range 25-57 days), but for 80% of the fry in each redd to emerge the mean time elapsed was 10.8 days (range 6 21 days). No fry sampled had a visible yolk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…In accordance with previous studies, we have considered the influence of discharge (MacCart, 1967;CampbeU & Scott, 1984;Irvine, 1986;Heggenes, 1988a) and of moonlight, although moon influence has only been revealed with a seasonal rhythm (Mason, 1975;Unwin, 1986;Field- Dodgsoti, 1988). Discharge varied during a trapping session only on 19 April, and flow increased only at 06:()0, i.e.…”
Section: Discussionsupporting
confidence: 64%
“…In accordance with previous studies, we have considered the influence of discharge (MacCart, 1967;CampbeU & Scott, 1984;Irvine, 1986;Heggenes, 1988a) and of moonlight, although moon influence has only been revealed with a seasonal rhythm (Mason, 1975;Unwin, 1986;Field- Dodgsoti, 1988). Discharge varied during a trapping session only on 19 April, and flow increased only at 06:()0, i.e.…”
Section: Discussionsupporting
confidence: 64%
“…These studies demonstrate that the alevins are able to feed before emergence if food is available. Indications of feeding before emergence have also been reported from some field‐studies, as food was found in the stomachs and intestines of newly emerged fry of both Atlantic salmon (Gustafson‐Marjanen & Dowse, 1983) and chinook salmon Oncorhynchus tshawytscha (Walbaum)(Field‐Dodgson, 1988). While the authors of both these studies argued that the fry probably had fed before emergence, Williams (1981) found little evidence for this in his studies of Atlantic salmon and brook trout Salvelinus fontinalis (Mitchill) in Matamek River in Quebec, since newly emerged fry were observed to have little material in their lower intestines compared to older juveniles.…”
Section: Discussionmentioning
confidence: 99%
“…In this way the alevins may save yolk reserves for periods when external food sources are temporarily limited. It has also been suggested that precocious feeding can have a positive effect by giving the fry practice in taking food particles, thereby giving the fry experience to feed more efficiently when external food becomes nutritionally necessary, or for building up intestinal enzyme activity (Heming et al ., 1982; Field‐Dodgson, 1988). No such effect was found by Heming et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peak emergence of brook charr alevins as the spring freshet receded was suggested by White (1930). Indirect evidence that alevin emergence was related to stream discharge was also presented for chinook salmon by Field-Dodgson (1988).…”
Section: Resultsmentioning
confidence: 91%